The Description of Self-Role in Lesbian Behavior in the Area of Semarang City - Ellyana Firdaus; Andriyani Mustika Nurwijayanti; Rina Anggraeni; Livana PH (GLOBAL HEALTH SCIENCE GROUP, 2022)
Homosexual behavior (lesbian) in the city of Semarang has increased every year. The negative impact of same-sex sexual orientation can experience social stress as a result of the stigma associated with same-sex orientation, as a result lesbians are prone to experiencing psychological problems such as negative self-role. This study aims to describe the role of self in lesbian behavior in the Semarang City Region. This type of research is quantitative with a descriptive design with a survey approach. The number of samples is 124 using random sampling technique. The results showed that the role of self was positive as many as 75 respondents (60.5%). It is recommended for lesbians to involve themselves in interacting not only with fellow lesbians but try to involve and get used to social activities and behave positively.